2006
DOI: 10.1016/j.actatropica.2006.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term reduction of Trypanosoma cruzi infection in sylvatic mammals following deforestation and sustained vector surveillance in northwestern Argentina

Abstract: Long-term variations in the dynamics and intensity of sylvatic transmission of Trypanosoma cruzi were investigated around eight rural villages in the semiarid Argentine Chaco in 2002-2004 and compared to data collected locally in 1984-1991. Of 501 wild mammals from 13 identified species examined by xenodiagnosis, only 3 (7.9%) of 38 Didelphis albiventris opossums and 1 (1.1%) of 91 Conepatus chinga skunks were infected by T. cruzi. The period prevalence in opossums was fourfold lower in 2002-2004 than in 1984-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 31 publications
2
50
0
3
Order By: Relevance
“…The predominance of lineage I among isolates from sylvatic habitats is probably due to the role of opossums as the major local sylvatic reservoir host of T. cruzi (Schweigmann et al 1999) and to the absence of T. cruzi infection among armadillos. Opossums have consistently been found infected almost exclusively with lineage I throughout the Chaco region and the Americas (Barnabé et al, 2000;Ceballos et al, 2006;Diosque et al, 2003;Wisnivesky-Colli et al, 1992;Yeo et al, 2005). Armadillos, especially Dasypus novemcinctus, are sylvatic hosts of T. cruzi II in the Paraguayan Chaco (Yeo et al, 2005) but they are very rare in the study area.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The predominance of lineage I among isolates from sylvatic habitats is probably due to the role of opossums as the major local sylvatic reservoir host of T. cruzi (Schweigmann et al 1999) and to the absence of T. cruzi infection among armadillos. Opossums have consistently been found infected almost exclusively with lineage I throughout the Chaco region and the Americas (Barnabé et al, 2000;Ceballos et al, 2006;Diosque et al, 2003;Wisnivesky-Colli et al, 1992;Yeo et al, 2005). Armadillos, especially Dasypus novemcinctus, are sylvatic hosts of T. cruzi II in the Paraguayan Chaco (Yeo et al, 2005) but they are very rare in the study area.…”
Section: Discussionmentioning
confidence: 77%
“…Natural infection by T. cruzi has been found in several local species of sylvatic mammals (Carcavallo and Martínez, 1968;Ceballos et al, 2006;Diosque et al, 2003;Yeo et al, 2005), whereas the putative sylvatic vectors have only been identified in Bolivia (Noireau et al, 2000). In the Gran Chaco, the bug Triatoma infestans is the main or single domiciliary vector; dogs, humans and chickens are usually the main blood meal sources of domestic bugs, and dogs and cats are considered the most important domestic reservoir hosts of T. cruzi (Minter, 1976;Gürtler et al, 1997Gürtler et al, , 2007a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Ongoing large-scale changes in land use and habitat fragmentation throughout Latin America may impact sylvatic transmission cycles in unforeseen ways, either reducing or increasing parasite prevalence. 19,23 Little is known about the structure and spatiotemporal dynamics of sylvatic transmission cycles of T. cruzi in the Gran Chaco. Few areas have been investigated in recent decades, usually through cross-sectional or convenience surveys; sampling efforts have focused on a limited number of species and environments, and identification of parasite DTUs from wild hosts has been sparse.…”
mentioning
confidence: 99%
“…12 In this region, the most frequently identified sylvatic hosts of T. cruzi are didelphid marsupials and various species of armadillos, followed by carnivores (including skunks, ferrets, foxes, and coatis) and a few species of small rodents. 7,9,[13][14][15][16][17][18][19][20] In general, host and parasite distributions may be modified by the combined effects of alterations in climate, landscape and biodiversity, which may create new habitats suitable for the development of parasites and vectors and increase the risk of transmission of pathogens. 21 The sylvatic distribution of triatomine bugs and transmission of T. cruzi appear to be closely associated with vegetation cover and landscape use.…”
mentioning
confidence: 99%